Omadacycline Potentiates Clarithromycin Activity Against Mycobacterium abscessus - Bich Hanh, Bui Thi; Quang, Nguyen Thanh; Park, Yujin; Heo, Bo Eun; Jeon, Seunghyeon; Park, June-Woo; Jang, Jichan (Frontiers in Pharmacology, 2021)
Mycobacterium abscessus is a difficult respiratory pathogen to treat, when compared to other nontuberculus mycobacteria (NTM), due to its drug resistance. In this study, we aimed to find a new clarithromycin partner that potentiated strong, positive, synergy against M. abscessus among current anti-M. abscessus drugs, including omadacycline, amikacin, rifabutin, bedaquiline, and cefoxitine. First, we determined the minimum inhibitory concentrations required of all the drugs tested for M. abscessus subsp. abscessus CIP104536T treatment using a resazurin microplate assay. Next, the best synergistic partner for clarithromycin against M. abscessus was determined using an in vitro checkerboard combination assay. Among the drug combinations evaluated, omadacycline showed the best synergistic effect with clarithromycin, with a fractional inhibitory concentration index of 0.4. This positive effect was also observed against M. abscessus clinical isolates and anti-M. abscessus drug resistant strains. Lastly, this combination was further validated using a M. abscessus infected zebrafish model. In this model, the clarithromycin-omadacyline regimen was found to inhibit the dissemination of M. abscessus, and it significantly extended the lifespan of the M. abscessus infected zebrafish. In summation, the synergy between two anti-M. abscessus compounds, clarithromycin and omadacycline, provides an attractive foundation for a new M. abscessus treatment regimen.